Application Program for Helping Road Complaints in Yogyakarta (APLANYA) - Alvino, Jevry; Deru, Muhammad; Wiranatakusuma, Dimas Bagus (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
In big cities like Yogyakarta in general, population growth and the number of private vehicles is very rapid, unfortunately not matched by the provision of adequate road infrastructure, so congestion is certain to occur, and this has really happened. If no action is taken or anticipated with an appropriate system, it is certain that total traffic jams will occur. The solution step to overcome this is to utilize the Application to help road complaints. To maximize the function of the Application, we try to implement an electronic-based system (online) to be able to access all public vehicles that pass on the entire urban road network according to the type of public vehicle (MPU, mini bus, medium bus, large bus, LRT, MRT, etc.). In an effort to support this system, it must be supported by adequate facilities, including all motorists are advised to download the application so that the movement of public vehicles is free from congestion. Another thing that is no less important is the condition or trip of the rider will arrive on time. With all the conveniences, the Application system is expected that people can access when they want to travel, so that congestion can be minimized.